(untitled) (Biological Sciences - PJSIR, 2002)
Physicochemical changes in Ultra high temperature (UHT) whole and skimmed buffalo milk stored at 10, 20 and 40°C for three months were studied. A significant decrease in pH and an increase in titratable acidity occurred during storage of UHT whole and skimmed milk at 20 and 40°C after three months of storage. At 10°C, viscosity of milk increased to some extent whereas decrease in vicosity was observed at higher temperaures . After three months storage at 40°C, total ash and lactose contents decreased by 18.5% and 6.67% from UHT whole milk and 20.93% and 15.66% from UHT skimmed milk, respectively . Similarly, decrease in casein nitrogen was 14.58% and 16.66% for lJHT whole and skimmed milk respectively , after three months storage at 40°C. On the other hand, non protei n nitrogen and non casein nitrogen increased by 68.72% and 47 .72% i n UHT whole milk and 64.28% and 31.25% in UHT skimmed m ilk , respecti vely. However total nitrogen content of UH.T milk remained unchanged during storage. A significant i ncrease i n hydroxy methyl furfural (HMF) values was observed depending upon the initial concentration of lactose in both types of milk and storage conditions . These changes were also observed during storage of UHT milk at 10 and 20°C but to a lesser extent. Subjective evaluation studies showed that UHT milk stored at 10 and 20°C was organoleptically acceptable after three months storage. On the other hand , sensory quality characteristics were adversely affected at 40°C after three months storag of UHT whole and skimmed milk